New Distributional Records of Richardia scabra Linn. in India - Bahadur, K. N.; Naithani, H. B. (Indian Forester, 1973)
Richardia scabra Linn. (Rubiaceae), a native of tropical America and now naturalised in many parts of the world, has hitherto been reported in India from Assam, Meghalaya, Andbra Pradesh and Rajasthan. It is now recorded from Uttar Pradesh, Bihar and Mysore States. Notes on its previous records from India and other tropical countries, nomenclature (genus as well as species), description, distribution, ecology, economic uses and affinities are provided with illustrations.